Perancangan Sistem Informasi Untuk Pengajuan Judul Tugas Akhir Pada Prodi Teknik Industri Berbasis Web Aplikasi - Miftakhul Ula; Sumiati Sumiati (International Forum of Researchers and Lecturers, 2024)
World civilization with very rapid changes in various countries is characterized by the unlimited use of information systems based on computing and big data. Information technology utilizes computers and computer software to convert, store, process, protect, transmit and obtain information securely. Designing an administrative service information system to assist students and final assignment coordinators in the registration process, filing requirements and submitting titles for final assignments and obtaining supervisor assignment letters. Therefore, this problem can be solved by building an information system design for final assignment administration services that will be implemented in the Industrial Engineering Study Program, namely SIMENTARI (Industrial Engineering Final Assignment Management Information System). In this research, the SIMENTARI design method used was waterfall. The waterfall method suggests systematic and sequential software development starting from the highest system level and continuing to the analysis, design, coding, testing and maintenance stages. The existence of a SIMENTARI Information System can make it easier for the Final Assignment Coordinator in the Industrial Engineering Study Program to serve students who will submit their Final Assignments more easily and systematically and the data entered by the user can be stored neatly in the system. In this research, the tools used to create a SIMENTARI information system were Xampp and Php MySQL software.